TRAC 2013 - Platts, Hannah; Platts, Hannah; Pearce, John; Pearce, John; Barron, Caroline M.; Barron, Caroline M.; Lundock, Jason; Lundock, Jason; Yoo, Justin; Yoo, Justin (Oxbow Books, 2014)
The twenty-third Theoretical Roman Archaeology Conference (TRAC) was held at King's College, London in Spring 2013. During the three-day conference nearly papers were delivered, discussing issues from a wide range of geographical regions of the Roman Empire, and applying various theoretical and methodological approaches. Sessions included those looking at Roman-Barbarian interactions; identity and funerary monuments in ancient Italy; migration and social identity in the Roman Near East; theoretical approaches to Roman small finds; formation processes of in-fills in urban sites; and new reflect